A qualitative expert interview approach towards understanding religious extremism among Malaysian youth - Yusof, Norhafezah; Kaur, Amrita; Mohd Sani, Mohd Azizuddin; Awang Hashim, Rosna (2019)
Religious extremism among Muslim youth is an emergent challenge and a variety of factors contribute towards its rise. However, few studies have explored this phenomenon in predominantly Muslim countries. Using expert interview approach, this study explored factors that provoke Malaysian youth into joining religious extremist groups and discussed findings from a social-ecological theory perspective. Inductive thematic analysis guided by socio-ecological theory was employed to analyze the data. Factors identified were Islamic Ideology-choice & Interpretation, Ummah and Practicality, and Charismatic leadership. The investigation through the social-ecological lens suggests that these causes mainly interacted at the macro-ecological and community-levels to influence the behaviour of Malaysian youths.